Tribological performance of modified jatropha oil containing oil-miscible ionic liquid, for machining applications - Abdul Sani, Amiril Sahab; Abd Rahim, Erween; Samion, Syahrullail (Springer Nature, 2017)
Modifying physicochemical and tribological properties of a bio-based lubricant is essential in improving its lubrication performances. This paper presents the effectiveness of a fully oil-miscible Ionic liquid (IL) as lubricant additive into a bio-based lubricant. Methyltrioctylammonium bis(trifluoromethylsulfonyl)imide (AIL) was selected as IL additive to improve the tribological performance of the bio- based lubricant. Additive was mixed into the bio-based lubricant at three levels of mass concentrations (1 wt.%, 5 wt.% & 10 wt.%). Tribology tests on steel/steel contacts were conducted to evaluate the lubricant samples. Test outputs were benchmarked against the neat bio-based lubricant. Results revealed good synergistic effect of the AIL additive blended into the bio-based lubricant. MJO+AIL10 % has shown good corrosion inhibition, superior friction reduction (48 %), lower worn surface area (23 %), excellent surface finish (46 %) and increased tapping torque efficiency (8 %). MJO+AIL10 % provided excellent tribological performances which corresponds to the energy saving and environmental benefit for sustainable machining applications.